Monday

April 21, 2014

April 21, 2014

Posted by **Andrew** on Monday, January 3, 2011 at 1:12pm.

6x - 3y = 7

(a) y = 2x - 4

(b)No solution

(c)x = 2, y = -4

(d)x = 2, y = 5/3

- Math -
**PsyDAG**, Tuesday, January 4, 2011 at 10:00amMultiply first equation by 3.

6x - 3y = 12

6x - 3y = 7

Does this make the answer clear?

**Related Questions**

math - A linear system may have a unique solution, no solution, or infinitely ...

math - Solve the systems of equations by elimination. 1. -2x+y=7 2. 2x+y=-9 6x+...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

math - hi, i need help with solving this equation for "y" 2x+3y=-2 2x+3y=-2 Get ...

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...

math - how do I solve this problem 2x/2=(6-3y)/2? 2x/2=(6-3y)/2? I solved it for...

Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...

correction of math - rewrite the equation 2x-3y= -6 as a function of x. My ...

math-calculus - i think i do something wrong again(2x+1)/(x-3)-(4x-1)/(2x-3) = 0...

math - A linear system may have a unique solution, no solution, or infinitely ...